A JOINT EFFORT OF FAITH COMMUNITIES IN OVERCOMING POVERTY: A CALL FOR PARTICIPATION: UPAYA BERSAMA KOMUNITAS AGAMA DALAM MENGATASI KEMISKINAN: PANGGILAN UNTUK PARTISIPASI - Ligawan, Andry (Jurnal Teologi Pambelum, 2024)
Poverty has become a critical issue in human life today, and tackling it is not the sole task of the government or institutions outside the religious realm. More than just a social responsibility, the existence of religion is key to actively participating in overcoming the problem of poverty, creating a providence for the creator in this world. To unravel this problem, the author will explore liberation theology as a framework to help religion play its critical role in alleviating poverty. Liberation theology, which grew up in social and economic inequality, offers a solid conceptual foundation to guide religion in poverty reduction efforts. Through this approach, religion is directed to be a voice that champions human rights and social justice and actively contributes to shaping progressive policies. Therefore, religion is a spiritual guide and a moral force that encourages real action. Religious participation in overcoming poverty is fulfilling a social calling and expressing the values of humanity and justice contained in religious teachings. Thus, liberation theology thinking becomes a relevant and essential tool to guide religion in manifesting its mission as an agent of change in defending those marginalized and impoverished. As a result, the joint efforts of religions to overcome poverty are not only a moral obligation but also a concrete manifestation of the commitment to create a more just and empowered world.